Treatment of Atopic Dermatitis From the Perspective of Traditional Persian Medicine - Rasool Choopani MD, PhD; Mehrzad Mehrbani MD, PhD; Alireza Fekri MD; Mitra Mehrabani PhD (SAGE Publishing, 2017)
There is a strong current trend for using complementary and alternative medications to treat atopic dermatitis. Atopic dermatitis is a common, chronic, pruritic, and inflammatory skin disease. It can have a profound, negative effect on patients' quality of life. Mild cases of atopic dermatitis can be controlled by the application of moisturizers and topical corticosteroids. However, in severe cases, application of immunosuppressive medication is unavoidable but it can have adverse effects. In traditional Persian medicine, diseases similar to resistant atopic dermatitis are treated with whey in combination with decoction of field dodder. Both whey and field dodder have anti-inflammatory properties. Consumption of whey can also aid skin repair, mitigate pruritus, and help combat the high level of stress experienced by patients. Therefore, it is hypothesized that consumption of traditional medicinal treatment of whey with decoction of field dodder can be applied as a complementary treatment for atopic dermatitis.